2004
DOI: 10.1007/s00774-003-0449-z
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass and metabolism in thalassemic children and adolescents treated with different iron-chelating drugs

Abstract: We evaluated bone mineral density (BMD) and bone turnover in 22 homozygous prepubertal beta-thalassemic patients treated with desferrioxamine. Ten patients underwent treatment with desferrioxamine for the whole study period, while 12 patients stopped desferrioxamine and were then treated with deferiprone (L1). Lumbar and femoral BMD and bone metabolism markers were examined at baseline and after 1 and 3 years of follow up. All patients were prepubertal at baseline and they all became pubertal over the 3 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 15 publications
5
34
1
4
Order By: Relevance
“…Regarding serum calcium there was no significant (p>0.05) difference between cases and controls (Table2). Similar result was seen by Mahachoklertwattana P et al 11 , Di Stefano M et al 12 , Eren E et al 13 . However some workers found hypocalcemia in their thalassemic patients.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding serum calcium there was no significant (p>0.05) difference between cases and controls (Table2). Similar result was seen by Mahachoklertwattana P et al 11 , Di Stefano M et al 12 , Eren E et al 13 . However some workers found hypocalcemia in their thalassemic patients.…”
Section: Discussionsupporting
confidence: 84%
“…Generally the mean age of participants in other studies was higher and the majority of patients had low BMD. 11,20,31,33 Vogiatzi and associates found that adolescence is a critical period for the augmentation of loss of bone mass in thalassemia and suggested that bone turnover plays an important role in this process. 33 These findings may better explain why our patients, who were all < 16 years of age, showed no significant changes in BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Its chelating action is not totally specific for iron. In fact, deferoxamine inhibits DNA synthesis, collagen formation and osteoblast precursor differentiation, while it enhances osteoblast apoptosis (17,18). Data on bone safety of new oral chelating agents are still limited.…”
Section: Deferoxaminementioning
confidence: 99%
“…The pathogenesis of bone changes in TM is not fully clarified. Several studies have shown that multiple factors may act in concert to produce bone disease in TM: bone marrow expansion (8), hypogonadism (9,10), defective GH-IGF-1 axis (11-15), altered pattern of cytokines (16), iron deposit in bone (6-8, 15), deferoxamine bone toxicity (17,18) and vitamin D deficiency (19).Some of these pathogenic factors, directly and/or indirectly, affect osteoblastic population, leading to depressed bone formation, while others often increase osteoclastic bone resorption. In this review, in the light of our experience, we analysed the alterations of bone metabolism and the acquired and genetic factors that could be responsible for the development of osteopenia/osteoporosis in TM patients.…”
Section: Introductionmentioning
confidence: 99%